The Relationship Between Cognitive Disorders and Physical Activity of the Elderly and Non-Communicable Diseases on the Risk of Falls in the Elderly - Siti Juwariyah; I’ien Noer’aini; Asti Nuraeni; Maya Cobalt Angio Septianingtyas (Indonesian Journal of Global Health Research, 2025)
Aging is a life process characterized by a decrease in the body's ability to adapt to the environment. As humans age, there will be a degenerative aging process that will have an impact on changes in humans not only physically but also cognitively. Decreased physical and cognitive function gives rise to several diseases in the elderly that are not contagious. Problems that are often experienced by the elderly are often associated with the aging process, one of which is cognitive function. Which is marked by obstacles in carrying out daily tasks. Method: The research method used a cross-sectional research design. The sample in this study was elderly from 60 – 85 years old, using a simple random sampling technique. Results using the mann whitney test showed a probability value of p: 0.005 that was smaller than the significant standard of α = 0.05. H1 is accepted, which means that there is a relationship between cognitive disorders and physical activity of the elderly with non-communicable diseases to the risk of falling in the elderly.